Frames in diagnostic reasoning - Cholewa, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
A frame is a flexible representation of statements and rules. It is especially attractive for the designing of interfaces with an expert system. It has been shown in the paper, that frames are a useful tool in the designing of reasoning systems for technical diagnostics. They can be successfully applied to support the most difficult part of such a task - i.e. to acquire knowledge. The main features of an expert system shell composed of a frame interpreter and tools for programmers have been presented, too.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka